Pengaruh Brand Awareness, Promosi Online Dan Harga Terhadap Keputusan Pembelian Di Marketplace Shopee Pada Mahasiswa Universitas Panca Marga - Rahdian Putri Siswati; Titik Musriati; Mutinda Teguh Widayanto (Universitas Panca Marga, 2024)
The aim of this research is to determine and analyze the influence of brand awareness, online promotions and prices on purchasing decisions in the Shopee marketplace among Panca Marga University students, both partially and simultaneously. The research method used is a quantitative method that is associative in nature. The population in this research were Panca Marga University students. The samples taken were 100 respondents. The sampling technique used was non-probability sampling using purposive sampling technique. The data sources in this research come from primary and secondary data. Data collection uses questionnaires and documentation which is then processed using data analysis methods, namely validity, reliability, classical assumption tests, normality tests, multiple linear regression analysis, coefficient of determination and hypothesis testing. Testing was carried out using SPSS and the results showed that brand awareness, online promotions and prices had both partial and simultaneous effects on purchasing decisions in the Shopee marketplace.